Hubungan Islam Dengan Kebudayaan Jawa - jakaria jakaria; Hesti Akila Jahra; Dennisa Amalia Syaka; Anis Fauzi (AL-KAINAH: Journal of Islamic Studies, 2023)
Islam and Javanese culture cannot be separated, both of them have a role and influence in navigating the times, Islam has brought many changes, starting from the kingdoms that began to stand on the island of Java. And the Islamic religion in Java has a unique diversity because the spread of Islam in Java is more dominant, resulting in the formation of diverse cultural acculturation. This acculturation occurs in many ways, one of which is visible, namely a result or work of carving, wayang, and slametan art. In the relationship between Islam and Javanese culture, each has a role and influence in spreading the religion of Islam, from the beginning of its development to enriching new cultures, and of course there are also some cultures that do deviate from the teachings of Islam, but Islam and Javanese culture can walk side by side.